(untitled) (Journal of Educational Sciences, 2024)
The article presents a study, the main idea of which is that for effective integration of technology into teaching, technology-related knowledge alone is not enough, potential teachers should possess different types of knowledge: technological, pedagogical and content knowledge, which are covered by the theoretical framework TPACK (Technological, Pedagogical and Content Knowledge) required to engage pre-service chemistry teachers in the integration of digital educational technologies into the educational process. The purpose of this study was to assess the effectiveness of the TPACK module we developed, as well as to identify how future chemistry teachers’ perceptions of technology integration changed after completing the educational technology module. The study involved 118 4th year students majoring in chemistry teacher training at K. Zhubanov Aktobe Regional University (Kazakhstan). Two cohorts were formed, namely control and experimental ones. The compulsory module of chemistry teaching, which is conducted for all students of the specified specialty in the form of a weekly lecture of standard duration, was supplemented for the experimental group over 10 weeks by a seminar devoted to the integration of technology into the teaching. During the experimental seminar, students were trained to develop diagnostic tasks using quiz applications, create short illustrative videos on chemical topics, use simulators and remote laboratories, etc. A total of 10 workshops were conducted. To measure subject-specific skills in technology integration, a test consisting of 8 open-ended questions was developed and students completed it before and after the study. Additionally, five participants in the experimental cohort with average scores were interviewed. The results of the study indicated that the mean post-experimental test score of the experimental cohort participants was significantly higher than that of the control group. The interview showed that students who took the experimental module not only mastered digital technologies, but also learned to integrate them quite effectively into the educational process. Key words: theoretical TPACK framework, educational technology, pre-service chemistry teachers, teacher education, digital technologies.